2011
DOI: 10.1021/bi200343h
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Resistance-Associated Macrophage Protein from the Protozoan Parasite Perkinsus marinus Mediates Iron Uptake

Abstract: Microbial pathogens succeed in acquiring essential metals such as iron and manganese despite their limited availability because of the host's immune response. The eukaryotic natural resistance-associated macrophage proteins mediate uptake of divalent metals and, during infection, may compete directly for metal acquisition with the pathogens' transporters. In this study, we characterize the Nramp gene family of Perkinsus marinus, an intracellular parasite of the eastern oyster, and through yeast complementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Thus, it is likely that as we observed for CvGal1 (22), the CvGal2 transcripts identified in these tissues actually originate in the infiltrating hemocytes. The P. marinus trophozoites enter the oyster through filter-feeding and initially become in contact with the gills, palps, gut or mantle, where they are phagocytosed by resident hemocytes (65) and survive intracellular oxidative stress by their effective anti-oxidative mechanisms (53, 54, 66, 67). The trophozoites proliferate in phagosome-like structures, eventually lysing the host hemocytes, and causing systemic infection and death of the oyster, which by releasing large numbers of parasites into the water column spreads the infection to neighboring oysters (20, 35).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that as we observed for CvGal1 (22), the CvGal2 transcripts identified in these tissues actually originate in the infiltrating hemocytes. The P. marinus trophozoites enter the oyster through filter-feeding and initially become in contact with the gills, palps, gut or mantle, where they are phagocytosed by resident hemocytes (65) and survive intracellular oxidative stress by their effective anti-oxidative mechanisms (53, 54, 66, 67). The trophozoites proliferate in phagosome-like structures, eventually lysing the host hemocytes, and causing systemic infection and death of the oyster, which by releasing large numbers of parasites into the water column spreads the infection to neighboring oysters (20, 35).…”
Section: Resultsmentioning
confidence: 99%
“…Dominin is of particular interest because it is a major plasma protein in the oyster hemolymph that exhibits a Cu,Zn-superoxide-like domain and has high similarity to cavortin, an iron-binding protein from the Pacific oyster (C. gigas) (47). We have characterized the role of iron for P. marinus virulence (48 -50) and intracellular survival in oyster hemocytes (51) and identified the iron uptake mechanisms via the Nramp transporter (52,53), responsible for a "tug of war" for available iron between the parasite and its oyster host (54). A rigorous glycomic analysis of dominin associated with hemocytes and from plasma revealed that it also displays biantennary glycans carrying blood group A moieties (61), thus opening the possibility that CvGal1 cross-links dominin to the hemocyte surface as a mechanism to sequester plasma iron into the intracellular pools, a defense mechanism against infectious challenge that has been conserved from invertebrates to mammals (55).…”
Section: Discussionmentioning
confidence: 99%
“…Dominin is a major plasma protein that houses a Cu/Zn superoxide-like domain, and is highly similar to cavortin, an iron binding-protein from the Pacific oyster (C. gigas) (Itoh et al, 2011). Iron is critical for P. marinus intracellular survival in oyster hemocytes (Schott and Vasta, 2003;Schott et al, 2003a;Fernández-Robledo et al, 2008;Alavi et al, 2009), and the iron transporters (Nramp; Robledo et al, 2004;Lin et al, 2011) in both the parasite and the oyster host are involved in their competition for available iron (Cellier et al, 2007). Another interesting ligand for CvGal1 identified on the hemocyte surface is β-integrin (Zhuo et al, 2008;Feng et al, 2013), and this was of particular interest as this transmembrane signaling glycoprotein is a key receptor in cell activation processes (Mayadas and Cullere, 2005;Lim and Hotchin, 2012).…”
Section: Identification Of Galectin Ligands On the Hemocyte And Parasmentioning
confidence: 99%